(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
COVID-19 is a major public health problem globally and also in Bangladesh. This cross-sectional descriptive study was conducted at Keraniganj Upazilla, Dhaka, with the objective of assessing the level of knowledge, attitude, and practice related to COVID-19 among adults of a rural and sub-urban community. Data were obtained through face-to-face interviews using a semi-structured questionnaire. The study has 618 participants. Regarding attitudes, 297 respondents (48.1%) believe that COVID-19 is a very dangerous disease, whereas 341 respondents (55.2%) believe that vaccines are of great aid. Masks are very helpful, according to 351 respondents (56.8%), isolation and social-distancing are also very helpful, according to 336 respondents (54.4%), and 553 respondents (89.5%) have a good attitude toward obtaining treatment. Only 25 (4%) of the respondents are found not to have received their COVID-19 vaccination in practice. This study shows that, it is advised that more focus be placed on awareness-raising programs to promote a positive attitude and appropriate COVID-19 practice. The Journal of Ad-din Women’s Medical College; Vol. 10 (2), July 2022; p 8-14